Awareness and Adoption of Dairy Promoting Schemes among Dairy Farmers in Punjab - Bajwa, G. S.; Rathore, R. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during 2024 (February-March) among dairy farmers of Ludhiana and Kapurthala district of the Punjab, India to analyse the level of awareness and adoption of dairy promoting schemes and factors influencing adoption of dairy promoting schemes. Two districts Ludhiana and Kapurthala were selected conveniently. Total 120 respondents were selected using snowball sampling method. Results of the study revealed that majority of the respondents were male farmers. The majority of dairy farmers had (44.20%) less the five year of dairy experience followed by (35.80%) had ten year of dairy farming experience. The majority of farmers (45.80%) had less than 20 dairy animals followed by (38.30%) had 20–50 animals. Only (30.8%) farmers were aware and familiar with DD8 dairy scheme. Scheme help in improve welfare and health of dairy animals (3.44) followed by dairy farmers understand they have resources to adopt and utilize benefits of schemes (3.40) and they understand scheme help in increasing farm size in terms of animals and productivity (3.36) were important benefits of the schemes. There was lack of awareness about scheme (3.75) followed by, complexity in documentation process (3.73), inadequate extension services and training programs (3.66) and the rates of subsidy were low which affect adoption of scheme (3.34) were reported important factors which affect adoption of dairy schemes among farmers.